Recent progress of microfluidic chips in immunoassay - Wu, Kaimin; He, Xuliang; Wang, Jinglei; Pan, Ting; He, Ran; Kong, Feizhi; Cao, Zhenmin; Ju, Feiye; Huang, Zhao; Nie, Libo (Frontiers in Bioengineering and Biotechnology, 2022)
Microfluidic chip technology is a technology platform that integrates basic operation units such as processing, separation, reaction and detection into microchannel chip to realize low consumption, fast and efficient analysis of samples. It has the characteristics of small volume need of samples and reagents, fast analysis, low cost, automation, portability, high throughout, and good compatibility with other techniques. In this review, the concept, preparation materials and fabrication technology of microfluidic chip are described. The applications of microfluidic chip in immunoassay, including fluorescent, chemiluminescent, surface-enhanced Raman spectroscopy (SERS), and electrochemical immunoassay are reviewed. Look into the future, the development of microfluidic chips lies in POCT and high throughput equipment, and there are still some challenges in the design and the integration of microfluidic chips, as well as the analysis of actual sample by microfluidic chips.